2020
DOI: 10.1177/0095399720957606
|View full text |Cite
|
Sign up to set email alerts
|

Developing the Public Participation Field: The Role of Independent Bodies for Public Participation

Abstract: This article examines how independent bodies for public participation (IBPPs) can initiate a convergence around practices among actors in the public participation field, especially sponsors of participatory arrangements and the associated participation firms. As IBPPs have the public resources and legal authority to independently organize participatory arrangements, they can play a coordinating role in the public participation field. A comparison of two IBPPs, one in Canada (Quebec) and one in France, shows th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 25 publications
0
9
0
Order By: Relevance
“…This legitimation extends beyond the credentialling of individual practitioners; it is also a vehicle for ‘deeper integration of engagement into organizational structures and cultures, including facilitating a greater number of engagement practitioners to enter executive and senior executive leadership roles in the same manner as their engineering, finance and project management counterparts’ ( Bice et al, 2019 : p. 305). As Bherer et al (2021) observed in their case studies of two government agencies that provide regulatory oversight over public participation, these agencies further the development of both formal and informal rules, norms and standards. While these agencies ‘rarely internalize public participation in their own organization’ ( Bherer et al, 2021 : 702), they do change public participation practice, as individual public participation professionals and specialized public participation firms adapted their work to ensure that their clients meet these new standards.…”
Section: The Rise Of the Public Participation Professionmentioning
confidence: 91%
See 4 more Smart Citations
“…This legitimation extends beyond the credentialling of individual practitioners; it is also a vehicle for ‘deeper integration of engagement into organizational structures and cultures, including facilitating a greater number of engagement practitioners to enter executive and senior executive leadership roles in the same manner as their engineering, finance and project management counterparts’ ( Bice et al, 2019 : p. 305). As Bherer et al (2021) observed in their case studies of two government agencies that provide regulatory oversight over public participation, these agencies further the development of both formal and informal rules, norms and standards. While these agencies ‘rarely internalize public participation in their own organization’ ( Bherer et al, 2021 : 702), they do change public participation practice, as individual public participation professionals and specialized public participation firms adapted their work to ensure that their clients meet these new standards.…”
Section: The Rise Of the Public Participation Professionmentioning
confidence: 91%
“…As the demand for community engagement grows, so too does the demand for a ‘new category of expert’ ( Bherer and Lee, 2019 : 196) to design and implement these processes. While some of these public participation specialists work as individual consultants, recent research by Bherer et al (2021) has tracked the emergence of public participation firms. These firms offer a variety of support services and ‘have gradually become recognized as specialists in public debate and who, in turn, subcontract some aspects of the process to smaller firms’ ( Bherer et al, 2021 : 700).…”
Section: The Rise Of the Public Participation Professionmentioning
confidence: 99%
See 3 more Smart Citations